A new species of the genus Obolopteryx Cohn et al. 2014 and a conspecific gynandromorph (Ensifera: Tettigoniidae: Phaneropterinae) - Barrientos-Lozano, Ludivina; Rocha-Sánchez, Aurora Y.; Correa-Sandoval, Alfonso (Zootaxa, 2015)
Obolopteryx truncoangulata n. sp., Barrientos-Lozano & Rocha-Sánchez, and a field collected conspecific gynandromorph are described, both from the northern Mexico’s Highland. O. truncoangulata n. sp., may be separated from congeneric O. brevihastata based on morphological characters. The male’s pronotum is more constricted mesally, and the tegmina are shorter. The disto-dorsal abdominal tergites sub-triangular projection broadly bilobated. Cerci broader proximally, and thumb and shaft more robust and shorter; subgenital plate deep “U” shape emarginated distally, lateral angles excised about mid portion. In females, tegmina, ovipositor, subgenital plate and basal sclerites are of different shape than analogous structures in O. brevihastata. Information on geographic distribution and ecology is provided.